Exploring the views of social workers employed by the Department of Social Development on having social workers in Gauteng’s township schools - Ramula, Magdeline (My University, 2017)
Township schools are confronted with a variety of problems which can be minimized by the intervention of school social workers. This qualitative research was aimed at looking at exploring the views of social workers employed by the Department of Social Development (DSD) on having school social workers in Gauteng’s township schools. The sampling of the research was in a form of voluntary sampling. The participants for this study were all selected from a population of social workers who are from the Department of Social Development (DSD). Ethics were considered and permission was granted by the Ethics committee as well as the Department of Social Development to conduct the study. Data was collected through semi-structured interviews which made use of an interview guide as a research tool. The data collected were analyzed using the method of thematic analysis. The findings contribute to the knowledge which is based on the contributing roles of social workers in township schools to facilitate and support the development of learners to achieve academically. To encourage the schools which do not have school social workers to have them. It also provides information to other school social workers about experiences in township schools. Key words: school social work, social worker, township schools, support
A report on a study project presented to The Department of Social School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfilment of the requirements for the degree Bachelor of Social Work